INTEGRATIVE LANGUAGE TEACHING MODELS IN DEVELOPING FUTURE TEACHERS’ ORAL COMPETENCE (INTERNATIONAL CONFERENCE ON MODERN DEVELOPMENT OF PEDAGOGY AND LINGUISTICS, 2025)
This article explores the effectiveness of integrative language teaching (ILT) models in enhancing oral competence among future English teachers. Drawing on the principles of communicative language teaching, task-based learning, and content and language integrated learning (CLIL), the study investigates how a multidimensional approach can foster fluency, accuracy, and pragmatic competence. A mixed-methods design is employed to assess the impact of integrative tasks, including microteaching, role-playing, and project-based discussions, on students’ speaking performance. Findings indicate that ILT models not only improve linguistic output but also enhance learner motivation and classroom engagement. The paper concludes with methodological recommendations for embedding integrative approaches into teacher education programs, ensuring alignment with real-world communication demands and professional teaching standards. The study contributes to the growing body of literature on the methodological innovation in EFL teacher training.